Low-invasive method of lengthening the crown as an alternative to implants (Эндодонтия Today)
The emergence of modern materials for therapeutic dentistry significantly increased the possibility of clinicians to conduct restoration of severely damaged teeth. We present a clinical case of recovery of the damaged tooth crown. After the root canal obturation by thermafills a surgical lengthening of the tooth crown was conducted. Then the tooth was restored with the help of fiberglass post fixed on the dual-curing cement and subsequently covered with all-ceramic crown. In cases of fracture of the clinical crown of the tooth crown lengthening surgery and restoration of the tooth with the use of «post-and-core» system is a good alternative to prosthetics on implants in cases of absence of the pain, tooth mobility within the normal range and the possibility of providing high-quality endodontic treatment.